Medicinal plants, biodiversity, and local communities. A study of a peasant community in Venezuela - Monagas, Olga; Trujillo, Iselen (Frontiers in Sustainable Food Systems, 2024)
The main objective of this research was to record ethnobotanical data on the use and exploitation of medicinal plants, highlighting their importance for the biodiversity, culture and tradition of a peasant community in Venezuela.The study population was 120 people and from there the sample was calculated with the formula for finite populations (n=34 people) and the sampling was simple random, and the TRAMIL (Traditions Medicine in Island) survey was applied to them.The ethnopharmacological table was constructed and an analysis was made through descriptive statistics.Results: 116 species of medicinal plants were recorded to treat different health conditions. The informants reflected through their responses that they use medicinal plants in the first instance to address a health condition, presenting varied forms of preparation of the plants, highlighting decoction (65.16%), raw (16.77%), macerated (8.38%) and infusion (7.09%). The most commonly used plant parts are leaves, flowers, fruits, bark, peels, roots and bulbs, while the most commonly used botanical families are Lamiaceae, Fabaceae, Rutaceae, Malvaceae, Verbenaceae, Acanthaceae, Asteraceae and Euphorbaceae. On the other hand, the species with the highest TRAMIL Significant Use Level were Oregano orejón (Coleus amboinicus Lour.) (68.29), Malojillo (Cymbopogon citratus (D.C.) Stapf.) (60.97), Tua tua (Jatropha gossypiifolia L.) (34.15), Colombiana (Kalanchoe pinnata (Lam.) Pers. ) (34.15), Poleo (Micromeria brownei (Sw.) Benth.) (29.27), Pasote (Chenopodium ambrosioides L.) (29.27), Llantén (Plantago major L.) (26.83), Te negro (Phyla stoechadifolia (L.) Small) (26.83), Yerbabuena (Mentha sp.) (21.85), Curia (Justicia pectoralis Jacq) (21.95).The community of El Onoto de El Valle de Tucutunemo, Aragua State, Venezuela has a high use of medicinal plant species to treat different health conditions as a first instance, being used mainly for flu and stomach ailments. It is important to emphasize that all the people approached through the different data collection instruments reported using them, both individually and their families, and in a wide range of ages, from children to the elderly, which reflects that the use of medicinal plants is part of their cultural heritage and ancestral roots.